Pengembangan Program Pendidikan Karakter untuk Meningkatkan Akhlak dan Moral Anak di Era Digital: Penelitian - Makhrus, Imam; Lindayati, Eka; Asy’ari, Hasan; Noviani, Dwi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The digital era has brought significant changes to children’s behavior and morality. Unlimited access to information often leads to a decline in character values and spirituality among younger generations. This study aims to develop a character education program that is relevant to the needs of children in the digital age in order to strengthen their morals and ethical conduct. The research employs a descriptive qualitative approach using literature review and document analysis techniques. Data were collected from various scholarly sources such as journals, books, and recent research reports. The findings indicate that character education becomes effective when integrated with digital technology through contextual approaches, project-based learning, and digital role modeling. Strengthening religious values, responsibility, empathy, and digital ethics forms the main pillars in program development. The conclusion of this study highlights the importance of synergy between families, schools, and communities in fostering virtuous character in children amidst the challenges of the digital world.